Competition for light drives yield components in strip intercropping in the Netherlands - Wang, Zishen; Dong, Bei; Stomph, Tjeerd-Jan; Evers, Jochem B.; van der Putten, Peter E.L.; van der Werf, Wopke (Field crops research, 2025)
The partitioning of light between species in intercrops changes over time in relation to the earliness of canopy development of each species, the final plant height, and the growth duration. Seasonal patterns of light capture in crop species mixtures may be reflected in the yield components of the species. We test the hypothesis that seasonal patterns of light capture in intercrops can explain intercropping effects on seed number, seed weight, and seed yield in different species mixture compositions, including relay and simultaneous intercrops. We determined the seed number per unit land area, thousand-seed weight, and seed yield of maize (Zea mays L.), wheat (Triticum aestivum L.), faba bean (Vicia faba L.), and pea (Pisum sativum L.), grown as four monocrops or as six bi-specific strip intercrops – maize/wheat, maize/faba bean, maize/pea, faba bean/wheat, faba bean/pea, and wheat/pea – in the Netherlands. Species were spring-sown and managed conventionally (i.e., non-organic). Maize was sown and harvested later than the three other species, which had approximately simultaneous growing periods. Light capture by each species before and during seed filling was estimated using a model based on strip width, plant height, and leaf area index. We then assessed the relationships between accumulated light captured per species, seed yield, and its components. Seed yields in intercrops and monocrops were strongly related to seed number for each species. In relay intercrops, both species had increased seed yield due to an increased number of seeds. Species grown in simultaneous intercrops did not have higher seed yield or seed number than the monocrop, except for faba bean intercropped with wheat or pea. Increased seed number of early-sown species in relay intercrops was related to greater light capture before seed filling compared to monocrops. Increased seed number in maize was associated with better light availability after maize overtopped the companion species. The early-sown species showed trade-offs between seed number and weight, whereas the improved light availability resulting from the early harvesting of companions allowed intercropped maize to fill all seeds to the same extent as monocropped maize did. Seed yield was more strongly related to seed number than seed weight in all species in both monocrops and intercrops. In relay intercrops, seed yield increases were realised by species filling seeds to take advantage of the larger seed number. The findings show the importance of achieving high seed number and effective seed filling for increasing seed yield in conventionally managed strip intercrops under Dutch growing conditions. •We determined how competition for light in strip intercrops affects yield and yield components.•Seed yield was more strongly correlated with seed number than with seed weight.•Temporally complementary light capture in relay intercrops increased seed number in both species.•Intercropped maize had increased light capture per seed during seed filling.•In simultaneous intercrops, seed number was increased in the species dominating light capture.